2015
DOI: 10.1007/s10895-015-1611-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral Studies and Quantum-Chemical Investigations on the Powerful Fluorophores: Imidazo[4,5-a]acridines

Abstract: The new 3H-imidazo[4,5-a]acridine-11-carbonitriles were prepared from the reaction of 1-alkyl-5-nitro-1H-benzoimidazoles with 2-(4-methoxyphenyl)acetonitrile and benzyl cyanide by nucleophilic substitution of hydrogen in high yields. Physical spectral and analytical data have confirmed the structures of the synthesized dyes. The optical and solvatochromic properties of these compounds were investigated and the results showed that they show very interesting photophysical properties. Density functional theory (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Based on our previous experiences that acridine moieties exhibit very interesting fluorescence properties, 18,19,21 compounds 3a-d were characterised by UV-Vis and fluorescence spectroscopy in the wavelength range of 200-1000 nm. Figure 1 shows the visible absorption and emission spectra of compounds 3a-d and numerical spectral data are presented in Table 1.…”
Section: Photophysical Properties Of Compounds 3a-dmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous experiences that acridine moieties exhibit very interesting fluorescence properties, 18,19,21 compounds 3a-d were characterised by UV-Vis and fluorescence spectroscopy in the wavelength range of 200-1000 nm. Figure 1 shows the visible absorption and emission spectra of compounds 3a-d and numerical spectral data are presented in Table 1.…”
Section: Photophysical Properties Of Compounds 3a-dmentioning
confidence: 99%
“…We recently focused on the synthesis of new fluorescent heterocyclic compounds [18][19][20][21][22] and the development of their application. 23 Prompted by the abovementioned optical properties of acridine and pyrazole heterocycles, we herein report a synthesis of a new pentacyclic heterocyclic system, the 3H-benzo[a]pyrazolo [3,4-j]acridines, with the purpose of studying their spectral and fluorescence properties.…”
mentioning
confidence: 99%
“…Imidazo [4,5-a]acridones (imidazo [4,5-a]acridin-11(6H)-ones) and imidazo [4,5-a]acridines are found to exhibit very high activities against Escherichia coli HB101 (BA-7601C), Staphylococcus aureus (PTCC-1074), Pseudomonas aeruginosa (PTCC 1431), and Bacillus subtilis (PTCC 1365), comparable to streptomycin as a reference drug [15]. Also, substituted-3H-imidazo[4,5-a]acridine-11-carbonitriles show very interesting fluorescence properties with high quantum yields [16][17][18]. To the best of our knowledge, no detailed theoretical study has been reported on the proposed mechanism to explain the formation of the substituted-3H-imidazo[4,5-a]acridine-11-carbonitriles or similar compounds.…”
Section: Introductionmentioning
confidence: 99%